2020
DOI: 10.1016/j.ijcha.2019.100448
|View full text |Cite|
|
Sign up to set email alerts
|

Patient care pathways in acute heart failure and their impact on in-hospital mortality, a French national prospective survey

Abstract: BackgroundOur purpose was to describe the care pathway of patients hospitalized for acute heart failure (AHF) and investigate whether a management involving a cardiology department had an impact on in-hospital mortality.MethodsBetween June 2014 and October 2018, we included patients hospitalized for AHF in 24 French hospitals. Characteristics of the episode, patient’s care pathway and outcomes were recorded on a specific assessment tool. The primary outcome was the association between patient care pathway and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 25 publications
4
11
0
Order By: Relevance
“…When comparing the baseline characteristics, our cohort showed a remarkably high prevalence of comorbidities such as diabetes mellitus and chronic kidney disease, which explains the relatively high event rate 38,40 . In line with our findings, higher age and NYHA class were found as predictors of fatal outcome 24,39 . Akintoye and colleagues also reported a significant association of CCI with in‐hospital mortality, but there has been no distinction between elective and non‐elective hospital admission in their study 41 .…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…When comparing the baseline characteristics, our cohort showed a remarkably high prevalence of comorbidities such as diabetes mellitus and chronic kidney disease, which explains the relatively high event rate 38,40 . In line with our findings, higher age and NYHA class were found as predictors of fatal outcome 24,39 . Akintoye and colleagues also reported a significant association of CCI with in‐hospital mortality, but there has been no distinction between elective and non‐elective hospital admission in their study 41 .…”
Section: Discussionsupporting
confidence: 81%
“…Data analysis showed an increased case severity according to the number of comorbidities as well as clinical presentation with a higher proportion of cases with NYHA class IV. As NYHA class was found to be a significant predictor of in‐hospital mortality previously and within our cohort, this might partly explain the higher in‐hospital death rate 24 . Several predictors for fatal outcome have been described.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Access to specialized care has a strong impact on patient prognosis, including a shorter hospital stay and a lower risk of hospital death, with no specific difference, however, in outcome after hospital discharge 7,17,18 . The heterogeneity of care pathway observed in this study and in that of Smeets et al suggested the need for multiple solutions, specific to each situation 19 .…”
Section: Discussionmentioning
confidence: 54%
“…A recently published study by Gorliki et al reported that a hospital course of care involving a cardiology department was associated with an increase in hospital survival in AHF patients. These finding may highlight the importance of collaboration between cardiologists and other in‐hospitals specialties, such as emergency physicians, in order to find the best in‐hospital pathway for patients with AHF 7 …”
Section: Discussionmentioning
confidence: 88%